The Influence of the Machining Drill and Direction of Rotation on the Surfaces of Ti6Al4V Dental Implants Subjected to Implantoplasty - Esteban Padullés-Gaspar; Francisco Real-Voltas; Esteban Padullés-Roig; Miguel Punset; Guillermo Cabanes; Pablo Fernández; Javier Gil (Journal of Functional Biomaterials, 2025)
Implantoplasty is widely used to treat peri-implantitis by removing biofilms from Ti6Al4V dental implants using rotating drills. This study examined the effects of diamond and tungsten carbide drills, and rotation direction (clockwise/counterclockwise), on surface modification, corrosion behavior, and cytotoxicity. Machining was performed for one minute under a controlled load. Surface roughness, nanohardness, compressive residual stress, and wettability were evaluated, along with SEM and EDX microanalyses of the residues. Corrosion behavior was evaluated using potentiostatic and potentiodynamic tests in Hank’s solution. Ion release was monitored over time, and fibroblast viability was tested using extracts at various dilutions. The higher abrasiveness of diamond drills leads to increases roughness from 0.22 mm (control) to 0.73 and 0.59 for diamond and tungsten carbide drills, respectively; in hardness from 2.2 GPa for the control to 4.8 and 3.9 GPa; and in residual compressive stress from −26 to −125 and −111 MPa, with diamond drills inducing more significant changes and producing more hydrophilic surfaces with contact angles around 54° in relation to 80° and 62° for the control and tungsten carbide, respectively. Tungsten carbide drills caused lower corrosion rates (0.0323 mm/year) than diamond drills (0.052 mm/year). In addition, we observed the presence of tungsten ion release. Cytotoxic effects on human fibroblasts were observed with both bur types, and were more pronounced with tungsten carbide, especially at lower dilutions. Only 1:10 dilutions maintained consistent cytocompatibility. The rotation direction showed no significant impact. These findings emphasize the critical influence of bur selection in implantoplasty on the biological response of surrounding tissues.